Effect of Acupuncture vs Sham Acupuncture on Live Births Among Women Undergoing In Vitro Fertilization: A Randomized Clinical Trial. Issue 8 (August 2018) - Smith, Caroline A.; de Lacey, Sheryl; Chapman, Michael; Ratcliffe, Julie; Norman, Robert J.; Johnson, Neil P.; Boothroyd, Clare; Fahey, Paul
Abstract : (Abstracted from JAMA 2018;319:1990–1998) Acupuncture during in vitro fertilization (IVF) is a frequently used adjunctive treatment. Evidence for its efficacy is conflicting.